PENGARUH PEMBERIAN ICE BREAKING TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMP - Siti Mariam; Maria Trisna Sero Wondo; Hilaria Melania Mbagho (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
This study aims to determine whether or not there is an effect of ice breaking on student learning outcomes in grade VIII mathematics learning at SMP Muhammadiyah Ende. The type of research used is experimental research with a quantitative approach, the location of this study is located at SMP Muhammadiyah Ende. The primary data in this study was in the form of observation sheets and tests of student mathematics learning outcomes distributed in grade VIII. The population in this study was 46 people consisting of class VIII A as many as 22 people and class VIIIB as many as 24 people. Meanwhile, the samples used are all grade VIII students of SMP Muhammadiyah Ende for the 2023/2024 academic year, where class VIIIA is an experimental class and class VIIIB is a control class. The instrument used is a test of student learning outcomes. The analytical techniques in this study are hypothesis prerequisite tests (normality test and homogeneity test) and hypothesis test (t-test). From the results of the study, it can be concluded that there is a significant influence between the learning model in the form of ice breaking on student learning outcomes in grade VIII mathematics learning at SMP Muhammadiyah Ende for the 2023/2024 academic year, as evidenced by t-test calculations that show the value of Sig. (2-tailed) is 0.000, which means it is smaller than < 0.05.